218 COMPUTED TOMOGRAPHY FEATURES OF PLACENTAL ABRUPTION FOLLOWING TRAUMA. (1st January 2005) - Shriki, J. E.; Helmy, M.; Yedavalli, R. V.; Cohen, A. J.
Abstract : Background: Placental abruption is characterized by separation of the placenta from the uterus and may result in compromise of the vascular supply to the fetus. Trauma has been implicated as a major risk factor for abruption. Traditionally, the diagnosis of abruption has been made clinically. However, with increasing use of computed tomography (CT) in evaluation of pregnant patients in the setting of trauma, it is important to recognize the radiographic appearance of abruption to allow for accurate diagnosis and treatment. Methods: We present the case of a 30 year-old gravida 1, para 0 female, pregnant at 36 weeks, managed at our institution following motor vehicle trauma. At initial presentation, the patient's vital signs were stable and fetal heart tracings were within normal limits. Physical examination revealed a large periumbilical and right abdominal ecchymosis and tenderness to palpation in the right flank and abdomen. No vaginal bleeding was detected. Results: Contrast-enhanced CT imaging of the abdomen demonstrated an intrauterine singleton pregnancy with absent enhancement of nearly three-fourths of the placenta consistent with abruption and devascularization. Injury to the right renal collecting system was also evident. Shortly after imaging, fetal heart tracings revealed repetitive late decelerations and decreased variability indicative of fetal distress. The patient underwent emergent Cesarian section that confirmed an abruption of 75% of the placenta and resulted in delivery of a viable, female infant. Conclusion: Placental abruption may result in fetal distress and carries an increased risk following trauma. CT imaging may allow for recognition and evaluation of the extent of abruption even before it becomes clinically evident.